ISSUES OF HARMONIZING NATIONAL STANDARDS WITH INTERNATIONAL STANDARDS IN PREPARING FINANCIAL STATEMENTS (American Journal of Business Management, Economics and Banking, 2025)
This scientific article discusses the need to prepare and adapt the balance sheet, compiled based on national standards, to international accounting standards and to provide it to external users within the established timeframe.